Business Strategies for the Next-Generation Network - Seel, Nigel (CRC Press, 2009)
Carriers and service providers have united around the concept of the Next-Generation Network (NGN). Although leveraging a broad basket of Internet technologies, the NGN is not being planned as the next-generation Internet. In its intention and architecture, it is more accurately described as Broadband-ISDN release 2.0.